Acute acalculous cholecystitis after abdominal wall repair (Rives-Stoppa). (16th April 2014) - Reurings, Jurrian C; Diaz, Ruben P D; Penninga, Luit; Nellensteijn, David R
Abstract : Acute acalculous cholecystitis (AAC) is a rare condition normally occurring in critically ill patients. Compared to acute calculous cholecystitis, AAC is associated with complications and has a worse outcome. Hence, knowledge of this condition is very important. We describe a case of a 31-year-old man who developed AAC after abdominal wall repair with mesh (Rives-Stoppa procedure) 1 day after discharge from the hospital. To the best of our knowledge, this is the first paper to report AAC after abdominal incisional hernia repair. Although it is known to be more common in critically ill patients, AAC can also occur postoperatively in outpatients. Early recognition and treatment of AAC may improve outcome.